Tilianin Reduces Apoptosis via the ERK/EGR1/BCL2L1 Pathway in Ischemia/Reperfusion-Induced Acute Kidney Injury Mice - Liu, Zengying; Guan, Chen; Li, Chenyu; Zhang, Ningxin; Yang, Chengyu; Xu, Lingyu; Zhou, Bin; Zhao, Long; Luan, Hong; Man, Xiaofei; Xu, Yan (Frontiers in Pharmacology, 2022)
Background: Acute kidney injury (AKI) is a common syndrome impacting about 13.3 million patients per year. Tilianin has been reported to alleviate myocardial ischemia/reperfusion (I/R) injury, while its effect on AKI is unknown, thus this study aims to explore if Tilianin protects I/R-induced AKI and the underlying mechanisms. Methods: The microarray dataset GSE52004 was downloaded from GEO DataSets (Gene Expression Omnibus). Differential expression analysis and gene-set enrichment analysis (GSEA) were performed by R software to identify apoptosis pathway related genes. Then RcisTarget was applied to identify transcription factor (TF) related to apoptosis. STRING database was used to construct a protein-protein interaction (PPI) network. Cytoscape software visualized PPI networks and hub TFs were selected via cytoHubba. AutoDock was used for molecular docking of Tilianin and hub genes-encoded proteins. The expression levels of hub genes were assayed and visualized by quantitative real-time PCR, western blotting and immunohistochemistry by establishing I/R-induced AKI mouse models. Results: Bioinformatics analysis showed that 34 genes, including FOS, ATF4 and Gadd45g were involved in the apoptosis pathway. 7 hub TFs might play important roles in Tilianin regulating apoptosis pathways. In vivo, Tilianin improved kidney function and reduced the number of TUNEL positive renal tubular epithelial cells (RTECs) after I/R-induced AKI. Tilianin reduced the activation of ERK pathway and then down-regulated the expression of EGR1. This further ameliorated the expression of anti-apoptotic genes such as BCL2L1 and BCL2, reduced pro-apoptotic genes such as BAD, BAX and caspase 3, and reduced the release of Cytochrome C. Conclusion: Tilianin reduced apoptosis after I/R-induced AKI by ERK/EGR1/BCL2L1 pathway. Our findings provided novel insights for the first time into the protective effect and underlying molecular mechanisms of Tilianin on I/R-induced AKI.